2019
DOI: 10.7554/elife.49753
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory neurons are more disinhibited than inhibitory neurons by chloride dysregulation in the spinal dorsal horn

Abstract: Neuropathic pain is a debilitating condition caused by the abnormal processing of somatosensory input. Synaptic inhibition in the spinal dorsal horn plays a key role in that processing. Mechanical allodynia – the misperception of light touch as painful – occurs when inhibition is compromised. Disinhibition is due primarily to chloride dysregulation caused by hypofunction of the potassium-chloride co-transporter KCC2. Here we show, in rats, that excitatory neurons are disproportionately affected. This is not be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 91 publications
3
55
0
Order By: Relevance
“…vs. inhibitory neurons because excitability in the former rely more heavily on inhibition 84 . Altogether, these observations support the prediction that the functional impact of disinhibition is larger where inhibition is more robust.…”
Section: Discussionmentioning
confidence: 99%
“…vs. inhibitory neurons because excitability in the former rely more heavily on inhibition 84 . Altogether, these observations support the prediction that the functional impact of disinhibition is larger where inhibition is more robust.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous firing is very low in both WDR and low-threshold mechanosensoryresponsive (LTM) neurons of Sp5C under control conditions; following CCI-IoN, however, spontaneous activity markedly increased in the WDR, but not in the LTM [39]. Moreover, it was recently found that excitatory neurons in laminae I-II in rat lumbar spinal cord showed fast adaptation to light tactile stimuli and very low spontaneous firing, whereas inhibitory neurons with a variety of non-adapting responses had much higher spontaneous activity ( [78]; see also [38]). Should these findings be applicable to the neurons recorded in TCC, it would indicate that these neurons are likely to be excitatory interneurons or projection neurons.…”
Section: Tcc Neurons Driven By Vibrissal And/or Gon Inputmentioning
confidence: 99%
“…Spontaneous ring is very low in both WDR and low-threshold mechanosensory-responsive (LTM) neurons of Sp5C under control conditions; following CCI-IoN, however, spontaneous activity markedly increased in the WDR, but not in the LTM [39]. Moreover, it was recently found that excitatory neurons in laminae I-II in rat lumbar spinal cord showed fast adaptation to light tactile stimuli and very low spontaneous ring, whereas inhibitory neurons with a variety of non-adapting responses had much higher spontaneous activity ( [78]; see also [38]). Should these ndings be applicable to the neurons recorded in TCC, it would indicate that these neurons are likely to be excitatory interneurons or projection neurons.…”
Section: Tcc Neurons Driven By Vibrissal And/or Gon Inputmentioning
confidence: 99%